Effects of droplet deformation, evaporation, and mutual interaction with air on droplet motion and droplet-film impingement in aeroengine bearing chambers. (April 2023) - Zhu, Donglei; Chen, Guoding; Wang, Lin; Zhang, Ruibo
Graphical abstract: Highlights: Effects of droplet evaporation, deform and coupling with air are included in the study. The proposed model is validated by existing experimental and numerical data. Superiority of proposed model is presented in terms of finer calculation and accuracy. Detailed phenomena are demonstrated and physical features are reasonably explained. Abstract: The physically complex oil/air two-phase flow field in aeroengine bearing chambers, incorporating droplet motion and droplet interaction with chamber wall oil film, significantly affects the lubrication and cooling function of bearing chambers. In the present investigation, a theoretical model is established upon the effects of droplet deformation, evaporation, and mutual interaction with air. Based on the model, the droplet motion characteristics and droplet quantities transferred into wall oil film can be obtained. Furthermore, the proposed model is validated by the high-quality experimental data from relevant literatures qualitatively and quantitatively. The mean percentage errors (MPE) of the calculation results, with experimental outcomes of two classical studies, are 9.62 % and 3.99 %. In addition, several interesting phenomena are observed: Droplet undergoes the shape oscillation, the mass and velocity reductions, as well as an increment of temperature during the motion. With the rising droplet diameter, an increase of droplet velocity and decrease of droplet temperature can be found, together with an enhancement of droplet quantities transferred into wall oil film. The proposed theoretical method not only facilitates the quantitative description of complex flow field in bearing chamber, but provides accurate input parameters for the following research of wall oil film flow. That contributes to the precise design of aeroengine bearing chamber lubrication system.